Kontribusi Sport Massage Menggunakan Teknik Dasar Manipulatif Terhadap Penurunan Asam Laktat Pada Atlet Atletik - Andri Prasetiyo; Reza Adhi Nugroho (Aisyah Journal Of Physical Education (AJoPE) e-ISSN : 3046-790X, 2023)
This study aims to determine the effect of basic manipulative sports Massage with basic manipulative techniques on reducing lactic acid levels in athletic athletes in Pesawaran district. This type of research uses the experimental type One Group Pretest-Posttest Design with a population of 14 atletik athletes. The sampling technique used total sampling. Based on the results of the data analysis carried out, there are differences in the results of the group that received treatment treatment and the control group. The value obtained from the experimental group with the number of respondents was 7, the pre test value was 8.78 Mmol and the post-test value was 3.54 Mmol with a decrease in the results of 5.12 Mmol. While the results for the control group with the number of respondents were 7 athletes, the pre-test result value was 8.24 Mmol and the post-test result value was 4.22 Mmol with a decrease in the result of 3.94 Mmol. From the calculation of statistical data, the significance value is 0.024. This means that if the value is less than 0.05 or the value ≤ 0.05, it can be concluded that there is an effect of sports manipulative Massage techniques on reducing lactic acid in athletic athletes in pesawaran district. The results of the research obtained through the treatment for the treatment group and the control group showed a significant effect on the effect of the basic techniques of manipulative sports Massage on the decreased levels of lactic acid in athletic athletes in pesawaran district.